TOWARDS ACCEPTANCE OF ISLAMIC WEALTH MANAGEMENT - Sarimah Basah,; Putri Rozita Tahir, (Journal of Islamic, Social, Economics and Development, 2019)
Several misconceptions on Islamic Banking (IB), Islamic Finance (IF) and Islamic Wealth Management (IWM), as a subset of IF, presents a good opportunity to expose the values embedded in IWM. IWM with its root anchored to Maqasid Shariah(MS), is a readily available advisory platform that should be appealing to more than just Muslims once its ethical values are made explicitly tangible. This paper aims to highlight the holistic values within IWM so as to increase its acceptance by Muslims and non-Muslims. The paper which is conceptual in nature should add value to any full-fledged Islamic Banks in Malaysia that carry comprehensive products under its IWM platform. Matters highlighted in this paper can be used by financial advisors as a guiding principle to give comprehensive financial and non-financial advices to clients based on each client’s life cycle and financial and hereafter goals.